Vanuatu : 2002 Article IV Consultation-Staff Report; Staff Statement; Public Information Notice on the Executive Board Discussion; and Statement by the Executive Director for Vanuatu. (IMF Staff Country Reports; Country Report, 2002)
This 2002 Article IV Consultation highlights that despite frequent shocks and an uncertain policy environment in Vanuatu, macroeconomic stability has been maintained. Real GDP growth was 2 1\2 percent in 2000 owing to an agriculture-led recovery. However, the economy contracted by 2 percent in 2001, owing to the effects of several major cyclones and a global downturn in agriculture and tourism. Inflation remained subdued, increasing from 2 1\2 percent in 2000 to 3 3/4 percent in 2001. The current account surplus declined from 2 percent of GDP in 2000 to 3/4 percent in 2001.